Violencia doméstica y riesgo de conducta suicida en universitarios adolescentes Domestic violence and risk of suicidal behavior among university students - Francisco Espinoza-Gómez; Víctor Zepeda-Pamplona; Víctor Bautista-Hernández; Carlos Moisés Hernández-Suárez; Oscar Alberto Newton-Sánchez; Guadalupe R Plasencia-García (Instituto Nacional de Salud Pública, 2010)
OBJETIVO: Estimar el grado de asociación entre violencia doméstica física, verbal y sexual con la conducta suicida en adolescentes universitarios. MATERIAL Y MÉTODOS: Estudio de casos y controles pareado en estudiantes universitarios de Colima. Los casos fueron 235 adolescentes que presentaron tanto ideación suicida como intento suicida; los controles fueron 470 individuos de la misma edad y sexo. RESULTADOS: El abuso sexual mostró el mayor grado de asociación con conducta suicida (RM= 27.4), seguido de violencia verbal (RM= 9.28), uso de drogas (RM= 8.6), violencia física (RM= 5.5) y tabaquismo (RM= 3.6). La regresión logística multivariada mostró que la violencia verbal se asoció con conducta suicida en forma independiente, mientras que violencia física, abuso sexual, tabaquismo y uso de drogas parecen depender de aquella. CONCLUSIONES: La violencia intrafamiliar, particularmente la verbal, está fuertemente asociada con la conducta suicida en adolescentes y debe ser considerada dentro de programas preventivos contra suicidio. OBJECTIVE: To estimate the degree of association between domestic violence -physical, verbal or sexual- with suicidal behavior among university students. MATERIAL AND METHODS: A matched case-control study was done with students attending the University of Colima, Mexico. The cases were 235 teenagers who presented both suicidal ideation and suicide attempt; the controls were 470 individuals of the same age and sex. RESULTS: Sexual abuse showed the highest degree of association with suicidal behavior (OR= 27.4), followed by verbal violence (OR= 9.28), drug use (OR= 8.6), physical violence (OR= 5.5) and smoking (OR= 3.6). Multivariate logistic regression showed that verbal violence was associated with suicidal behavior independently of the other variables, while physical violence, sexual abuse, smoking and drug use seem to depend on verbal violence. CONCLUSIONS: Domestic violence, particularly verbal or sexual, is strongly associated with suicidal behavior in adolescents and should be considered in suicide prevention programs.